Chiral Gold Nanoparticles Decorated with Pseudopeptides. Issue 28 (12th August 2015) - Fanelli, Rossana; Milli, Lorenzo; Cornia, Andrea; Moretto, Alessandro; Castellucci, Nicola; Zanna, Nicola; Malachin, Giulia; Tavano, Regina; Tomasini, Claudia
Abstract: Peptide‐functionalized gold nanoparticles are supramolecular systems that can mimic natural proteins or DNA. In this work, we describe the preparation, the analysis, and the biological evaluation of gold nanoparticles linked to pseudopeptide foldamers containing one to eightL ‐Ala‐D ‐Oxd (Ala = alanine; Oxd = 4‐carboxy‐5‐methyloxazolidin‐2‐one) residues. The nanoparticles become increasingly organized as the number of such moieties increases. Moreover, from the analysis of chiroptical signals we find that the chirality of the gold surface becomes more evident with decreasing foldamer length. Finally, these systems display no cytotoxicity towards HeLa cells and are good candidates to promote drug delivery once equipped with biologically active moieties. Abstract : Biocompatible chiral gold nanoparticles (NPs) capped with pseudopeptide foldamers based on an increasing number ofL ‐Ala‐D ‐Oxd units (Oxd = 4‐carboxy‐5‐methyloxazolidin‐2‐one) were prepared and analyzed with respect to intramolecular H‐bonding interactions. According to ECD spectra, the interactions are retained when pseudopeptide foldamers are linked to Au NPs.